2015
DOI: 10.1080/14786419.2015.1107556
|View full text |Cite
|
Sign up to set email alerts
|

A review on biological sources, chemistry and pharmacological activities of pinostrobin

Abstract: Pinostrobin, a dietary bioflavonoid discovered more than 6 decades ago in the heart-wood of pine (Pinus strobus), has depicted many pharmacological activities including anti-viral, anti-oxidant, anti-leukaemic, anti-inflammatory and anti-aromatase activities. It is an inhibitor of sodium channel and Ca(2+) signalling pathways and also inhibits intestinal smooth muscle contractions. In spite of the fact that pinostrobin has an application as functional foods, till-to-date no comprehensive review on pinostrobin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 46 publications
2
31
0
1
Order By: Relevance
“…Among the flavonoids identified in the analyzed poplar buds, the contents of two, pinostrobin and pinocembrin, were determined. This was due to their confirmed antioxidant and anti-inflammatory properties, which might be responsible for medicinal efficacy of poplar buds (14,15). Two evaluation modes for quantitative analysis of flavanones, densitometric and videodensitometric, were employed.…”
Section: Qualitative Screening Of Poplar Bud Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the flavonoids identified in the analyzed poplar buds, the contents of two, pinostrobin and pinocembrin, were determined. This was due to their confirmed antioxidant and anti-inflammatory properties, which might be responsible for medicinal efficacy of poplar buds (14,15). Two evaluation modes for quantitative analysis of flavanones, densitometric and videodensitometric, were employed.…”
Section: Qualitative Screening Of Poplar Bud Extractsmentioning
confidence: 99%
“…Flavonoids can play an important role in the pharmacological effects of poplar buds in terms of their antioxidant and anti-inflammatory properties. Among Populus constituents, two flavanones, pinostrobin and pinocembrin, revealed interesting antioxidant and antiinflammatory activities (14,15).…”
mentioning
confidence: 99%
“…Pinostrobin is a natural flavonoid that exerts diverse bioactivities, including antioxidant (Wei et al, 2013), antimicrobial (Dzoyem et al, 2012) and anti-inflammatory activities (Patel, Jaiswal, & Bhutani, 2015), the induction of quinone reductase activity (Fahey & Stephenson, 2002) and virus protease inhibition (Heh et al, 2013). This compound also substantially induced the activities of mammalian phase II detoxification enzymes and antioxidant enzymes (Fahey & Stephenson, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Recent pharmacological studies revealed that the needles of P. massoniana possess antioxidant (Chen et al 2014), antibacterial , cardiovascular protection (Wang et al 2008), lipid regulation (Zheng et al 2010), and antitumour (Zheng et al 2009) properties. Up to now, volatile oil (Yatagai & Hong 1997), lignans (Lundgren et al 1985), flavonoids Patel et al 2016), shikimate (Ma et al 2008), proanthocyanidins (Gao et al 2011;Shen et al 2010) and their derivatives were isolated from P. massoniana. In our phytochemical investigation, two new sesquiterpene glycosides, compounds 1 and 2, were isolated from the title plant.…”
Section: Introductionmentioning
confidence: 99%